#### Answer

$xe^{y+2z}+C$

#### Work Step by Step

Here, $f=xe^{y+2z}+g(y,z)$
and $g(y,z)=0$ or, $g(y,z)=h(z)=0$
Then $f=xe^{y+2z}+h(z)$
This implies that
$f_z=2xe^{y+2z}+h'(z)=2xe^{y+2z}$
Hence, $f=xe^{y+2z}+C$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$xe^{y+2z}+C$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.